Collectivization of agriculture in Eastern Europe - Kraehe, Enno E. (University of Kentucky Press, 1958)
Collectivization of agriculture is an essential feature of the Communist program for the satellite countries of Eastern Europe. It is a means of extending state control of agriculture as well as the basis for developing large-scale industrial and military power. Irwin T. Sanders has edited this excellent group of papers by specialists on Eastern Europe and American rural social scientists, which collectively serve as an analysis of efforts to regiment the East European peasant.